Safety and efficacy of tracheotomy for critically ill patients with coronavirus disease 2019 (COVID-19) in Wuhan: a case series of 14 patients. (21st September 2020) - Aodeng, Surita; Wang, Weiqing; Chen, Yu; Feng, Guodong; Wang, Jian; Lv, Wei; Yang, Hua; Ding, Xin; Song, Kaicheng; Zhao, Sirui; Liu, Jiazhen; Zhang, Shuyang; et al.
Abstract: OBJECTIVES: Coronavirus disease 2019 (COVID-19) is a global pandemic. Critically ill patients often require prolonged intubation for mechanical ventilation to support breathing; thus, the artificial airway must be managed by tracheotomy. Therefore, studies exploring appropriate and safe methods for tracheotomy that minimize the risks of nosocomial transmission are important. METHODS: A retrospective analysis of the clinical characteristics of 14 critically ill patients with COVID-19, who underwent bedside tracheotomy from March to April 2020 was conducted to summarize the indications for tracheotomy and key points related to personal protective equipment and surgical procedures. RESULTS: All 14 patients were diagnosed with COVID-19 and were critically ill. All tracheotomies were performed in the late phase of the infection course. The interval between the infection and tracheotomy was 33 days, and the median interval between intubation and tracheotomy was 25.5 days. The reverse transcription-polymerase chain reaction results of secretions from the operative incision and inside the tracheotomy tube were negative. Twelve patients improved after tracheotomy, with SpO2 levels maintained above 96%. One patient died of progressive respiratory failure; another patient died of uncontrolled septic shock. No medical staff who participated in the tracheotomy was infected. CONCLUSIONS: Tracheotomy in critically ill patients with COVID-19 who meet the indications for tracheotomy potentially represents a safer approach to manage the airway and help improve the treatment outcomes. A tracheotomy performed in the late phase of the disease has a relatively low risk of infection. Adherence to key steps in the tracheotomy procedure and donning adequate personal protection will help medical staff avoid infection.